The physical and mechanical properties of chloride-based deicers at 0∼−30 °C. (30th June 2019) - Ma, Haoxia; Yu, Hongfa; Tian, Jinliang; Tan, Yongshan; Da, Bo
Highlights: The icing pressure of chloride deicers was measured. The heat of liquid–solid phase transformation was discussed. The cooling process of chloride deicers was divided into four stages. The concept of the I p cumulative effect with time was first proposed to determine the freeze-thaw destruction. Abstract: Icing pressure testing was conducted to investigate the icing pressure ( I p ) of chloride-based deicers and discuss the relation between I p and the freeze-thaw deterioration of concrete induced by chloride deicers. During the icing pressure test, when the solution transformed from the liquid to the solid phase, undercooling occurred, and the heat of the liquid-solid phase transformation was released. The I p of chloride deicers and water reached a plateau near −30 °C. The stable I p value of water was the highest of that of the chloride solutions followed by that of 3.5% NaCl; the I p of 3.5% CaCl2 was slightly higher than that of 3.5% MgCl2 . The concept of the I p cumulative effect with time ( S ) was first proposed to determine the freeze-thaw destruction induced by chloride-based deicers. The durable life of the concrete exposed to chloride-based deicers decreased with the S of the deicers, and the mass loss of the concrete increased with the S of the deicers.